2014
DOI: 10.1111/ajt.12591
|View full text |Cite
|
Sign up to set email alerts
|

“Very Early” Intrahepatic Cholangiocarcinoma in Cirrhotic Patients: Should Liver Transplantation Be Reconsidered in These Patients?

Abstract: A retrospective cohort multicenter study was conducted to analyze the risk factors for tumor recurrence after liver transplantation (LT) in cirrhotic patients found to have an intrahepatic cholangiocarcinoma (iCCA) on pathology examination. We also aimed to ascertain whether there existed a subgroup of patients with single tumors ≤2 cm (“very early”) in which results after LT can be acceptable. Twenty‐nine patients comprised the study group, eight of whom had a “very early” iCCA (four of them incidentals). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
125
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(134 citation statements)
references
References 32 publications
5
125
0
4
Order By: Relevance
“…iCCA has conventionally been considered a contraindication for liver transplantation owing to poor survival outcomes and a high risk of recurrence 44,45 . In 2014, however, a retrospective multicentre study demonstrated an excellent 5-year actuarial survival after liver transplantation of 73% in eight patients with cirrhosis and ‘very early’ iCCA, defined as single tumours ≤2 cm in diameter 46 . A follow-up study with a larger, international, multicentre cohort of patients found a 5-year survival of 65% in 15 patients with very early iCCA versus 45% in 33 patients with ‘advanced’ iCCA (single tumour >2 cm or multifocal disease) 10 .…”
Section: Standard Of Care: Diagnosis and Therapymentioning
confidence: 99%
“…iCCA has conventionally been considered a contraindication for liver transplantation owing to poor survival outcomes and a high risk of recurrence 44,45 . In 2014, however, a retrospective multicentre study demonstrated an excellent 5-year actuarial survival after liver transplantation of 73% in eight patients with cirrhosis and ‘very early’ iCCA, defined as single tumours ≤2 cm in diameter 46 . A follow-up study with a larger, international, multicentre cohort of patients found a 5-year survival of 65% in 15 patients with very early iCCA versus 45% in 33 patients with ‘advanced’ iCCA (single tumour >2 cm or multifocal disease) 10 .…”
Section: Standard Of Care: Diagnosis and Therapymentioning
confidence: 99%
“…These studies demonstrated excellent post-transplant survival for patients with such tumors on pathology. Nevertheless, future studies must be conducted to confirm these results [15,16] .…”
Section: Diagnosis Of Very Early Hccmentioning
confidence: 95%
“…Intense contrast uptake in the arterial phase followed by contrast washout in the venous phase, both on computed tomography or magnetic resonance, is considered diagnostic for HCC > 1 cm [9,14] . Nevertheless, on cirrhotic patients, small lesions may be misdiagnosed as being HCC and can in fact be intrahepatic cholangiocarcinomas (iCCA) or mixed hepatocellular-cholangiocarcinomas (HCC-CC), being their frequency much lower [15,16] . If the lesion does not show the typical HCC pattern on imaging, biopsy is mandatory [10] .…”
Section: Diagnosis Of Very Early Hccmentioning
confidence: 99%
“…The authors reported a 5-year RFS rate of 78% in low risk group, compared with 19% in intermediate, and 14% in high risk groups, suggesting that liver transplant is appropriate in select cases of locally advanced ICCA. More recently, a retrospective multicenter study demonstrated that liver transplantation for select cirrhotic patients with small solitary lesions (up to 2 cm) achieved a 5-year survival rate of 73% (21). Furthermore, at a median follow-up of 36 months, none of the patients had a tumor recurrence.…”
Section: Liver Transplantationmentioning
confidence: 99%